ANALISIS KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Soto Seger Mbok Giyem Di Boyolali) - Agus Dwi Antoro (Universitas Boyolali, 2019)
The development of business today is experiencing a very rapid growth. The developments are very significant and have a pretty good prospect. So such conditions make competition increasingly competitive especially in the field of culinary. Research was conducted to test the effect of quality of service and facilities to the purchase decision of Soto Seger Mbok Giyem in Boyolali. Accidental sampling technique with sample research samples 100. Multiple linear regression methods. The results of the research of quality of service and facilities simultaneously effect positive and significant against the purchase decision, quality of service and facilities to the decision of each of the influential positive and significant decisions Purchase. The decision to purchase Soto Seger Mbok Giyem in Boyolali can be explained by 38.5%, while the remaining 61.5% is explained by other variables. Keywords: purchasing decisions, quality of service, facilities